EFFECT OF CEREBRALECTOMY ON BIOCHEMICAL CONTENT IN THE GONAD OF THE FRESHWATER BIVALVE MUSSEL, LAMELLIDENS CORRIANUS, IN DIFFERENT SEASON - S. B. DONGRE; N. B. DONGRE (The Bioscan, 2012)
Lamillidens corrianus (Shell length 95-110mm) from Nandrabad pond, Aurangabad in different seasons were collected and were acclimatized in laboratory condition for 2 to 3h and surgerical operation were made for removal of cerebral ganglion unilaterally and bilaterally after lapse of 24h. The animals were placed into 3 groups. The biochemical constituent like protein content was determined after 7 days during each season from gonad. The protein content was significantly p<0.001 increased in winter and significantly p<0.001 decreased in summer in control group animal except in bilaterally cerebralectomized group. The lipid content was significantly p<0.001increased in post -monsoon and a significant p<0.001decrease in winter in control group animal except in unilaterally cerebralectomized group. The glycogen content was significantly p<0.001increased in winter and a non-significant decrease in monsoon in control group animal except in unilaterally cerebralectomized group. The seasonal variation in biochemical constituents have been studied in detail in gonads of Lamillidens corrianus.